Influence of dosing volume on the neurotoxicity of bifenthrin - Wolansky, Marcelo Javier (2007)
Pyrethroids are pesticides with high insecticidal activity and relatively low potency in mammals. The influence of dosing volume on the neurobehavioral syndrome following oral acute exposure to the Type-I pyrethroid insecticide bifenthrin in corn oil was evaluated in adult male Long Evans rats. We tested bifenthrin effects at 1 and 5 ml/kg, two commonly used dose volumes in toxicological studies. Two testing times (4 and 7 h) were used in motor activity and functional observational battery (FOB) assessments. Four to eight doses were examined at either dosing condition (up to 20 or 26 mg/kg, at 1 and 5 ml/kg, respectively). Acute oral bifenthrin exposure produced toxic signs typical of Type I pyrethroids, with dose-related increases in fine tremor, decreased motor activity and grip strength, and increased pawing, head shaking, click response, and body temperature. Bifenthrin effects on motor activity and pyrethroid-specific clinical signs were ∼ 2-fold more potent at 1 ml/kg than 5 ml/kg. This difference was clearly evident at 4 h and slightly attenuated at 7 h post-dosing. Benchmark dose (BMD) modeling estimated similar 2-fold potency differences in motor activity and pyrethroid-specific FOB data. These findings demonstrate that dose volume, in studies using corn oil as the vehicle influences bifenthrin potency. Further, these data suggest that inconsistent estimates of pyrethroid potency between laboratories are at least partially due to differences in dosing volume.